2015
DOI: 10.1104/pp.114.245241
|View full text |Cite
|
Sign up to set email alerts
|

Does Low Stomatal Conductance or Photosynthetic Capacity Enhance Growth at Elevated CO2 in Arabidopsis?

Abstract: The objective of this study was to determine if low stomatal conductance (g) increases growth, nitrate (NO 3 2 ) assimilation, and nitrogen (N) utilization at elevated CO 2 concentration. Four Arabidopsis (Arabidopsis thaliana) near isogenic lines (NILs) differing in g were grown at ambient and elevated CO 2 concentration under low and high NO 3 2 supply as the sole source of N. Although g varied by 32% among NILs at elevated CO 2 , leaf intercellular CO 2 concentration varied by only 4% and genotype had no ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…time scales (Ehleringer and Cerling, 1995;Ward, 2005;Gerhart and Ward, 2010;Gerhart et al, 2012;Easlon et al, 2015). These findings suggest that c i /c a may have interesting evolutionary pathways, whereby this trait appears to be evolutionarily homeostatic in some cases.…”
Section: Box 1: Case Study Testing the Set-point Hypothesis For C I /C Amentioning
confidence: 82%
“…time scales (Ehleringer and Cerling, 1995;Ward, 2005;Gerhart and Ward, 2010;Gerhart et al, 2012;Easlon et al, 2015). These findings suggest that c i /c a may have interesting evolutionary pathways, whereby this trait appears to be evolutionarily homeostatic in some cases.…”
Section: Box 1: Case Study Testing the Set-point Hypothesis For C I /C Amentioning
confidence: 82%
“…In general, the photosynthesis rate is limited by the ribulose-1,5-bisphosphate regeneration rate or ribulose-1,5-bisphosphate carboxylation rate at high and low [CO 2 ]s, respectively. If the balance between the capacities of RuBP regeneration and carboxylation varies among ecotypes as indicated by previous studies (Easlon et al 2014(Easlon et al , 2015, the CO 2 response of photosynthesis should vary (Hikosaka and Hirose 1998;Medlyn 1996). Further studies are required to elucidate the underlying mechanisms.…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, most studies have confirmed that elevated CO 2 may improve the water status of drought-stressed plants by reducing g s (e.g., Brodribb et al, 2009 ; Katul et al, 2010 ; Chen et al, 2015 ; Easlon et al, 2015 ), but these findings were species-dependent ( Beerling et al, 1996 ; Bernacchi et al, 2007 ; Liu et al, 2016 ). However, this case may not occur under severe or extreme drought conditions, possibly due to the depression of stomatal regulatory ability ( Xu and Zhou, 2008 ).…”
Section: Interactions With Other Factorsmentioning
confidence: 99%